Statins' Withdrawal Induces Atherosclerotic Plaque Destabilization in Animal Model—A "Rebound" Stimulation of Inflammation. (July 2019) - Stasinopoulou, Marianna; Kadoglou, Nikolaos P. E.; Christodoulou, Eirini; Paronis, Efthymios; Kostomitsopoulos, Nikolaos G.; Valsami, Georgia; Liapis, Christos D.; Kakisis, John
Background: To evaluate the impact of atorvastatin discontinuation on the progression and stability of atherosclerotic plaques in a valid animal model of atherosclerosis. Methods: Seventy ApoE −/− male mice fed with high-fat diet were randomly assigned into: (1) long-term intervention groups: (i) ATL, received atorvastatin for 12 weeks, (ii) CO-12W, control received vehicle for 12 weeks, (iii) ATW-6W, received atorvastatin for 6 weeks which was withdrawn for another 6 weeks. (2) Short-term intervention groups: (i) ATS received atorvastatin for 6 weeks, (ii) CO-6W, control receiving vehicle for 6 weeks, (iii) ATW-3D, ATW-7D, received atorvastatin for 6 weeks which was withdrawn for 3 days and 7 days, respectively. Daily dosage of atorvastatin was 20 mg/kg. Mice were killed and aortic samples were obtained for histological evaluation. Results: Long-term atorvastatin treatment (ATL) induced atherosclerosis regression and stabilization compared to control ( P < .05). Atorvastatin's withdrawal was associated with acute (ATW-3D) reduction in connective tissue and collagen contents within plaques compared to ATS ( P < .05). Those changes were almost restored after a while (ATW-7D) and started appearing again after longer cessation (ATW-6W). Moreover, atorvastatin withdrawal induced shortly (ATW-3D) a peak in inflammatory markers (macrophages, MCP-1, tumor necrosis factor-α) and matrix metalloproteinases (MMP-3, MMP-9) concentrations within plaques, which sustained but to a lesser extent along time (ATW-7D, ATW-6W). Conclusion: Short-term withdrawal of atorvastatin seems to compromise its antiatherosclerotic effects, leading to an unstable phenotype of the atherosclerotic lesions and a rebound increase in inflammatory mediators. The clinical relevance of our findings requires further investigation.